The in vitro diffusion across exercised porcine skin of various formulations of compounds used topically in the treatment of skin afflictions - Elonga, Jessica (University of the Witwatersrand, Johannesburg, 2023)
Introduction and Aim: Skin afflictions have been treated with topically applied active compounds since the ancient Greek era. Topical compounds mostly avoid first-pass metabolism and move directly into the local region of the skin or mucous membranes to exert their therapeutic effects. In this study, the aim was to investigate the in vitro diffusion characteristics of active compounds commonly used in topical formulations, such as caffeine, theophylline, retinol, L-carnitine, and Co-enzyme Q10 across porcine skin, used as a model for human skin. These compounds were tested alone and in combination within different topical formulations (liquid, gel, and cream) to investigate skin permeation, skin accumulation and effect on skin integrity. Methods: Method development and validation were performed to detect and quantitate all compounds tested by using a RP C18 HPLC system. Mobile phases included the following: caffeine and theophylline (Methanol:water [40:60], 20oC), retinol (Methanol:water [95:5], 20oC), L-carnitine (Sodium Phosphate buffer (pH 3.0):Methanol [99:1], 40oC) and Co-enzyme Q10 (Methanol:2-propanol [40:60], 25oC). All analyses were performed at 1 ml/min and injection volume of 20 μl. In vitro diffusion studies were performed using a PermeGear 7-in- line flow-through system. Either caffeine (2.5%), theophylline (2%), retinol (0.3%), L-carnitine (2%) or Coenzyme Q10 (0.5%) in various formulations alone, and in combinations were loaded into the donor compartments and PBS (pH 7.4) was pumped through the acceptor chambers at 1.5 ml/h (32°C, over 4 hours and 24 hours). The fluid collected (every 30 min or 2 hours) was analysed by RP HPLC. Skin accumulation for each compound was performed after completion of each experiment and skin integrity was established by measuring tissue resistance. Results: HPLC methods were found to be sensitive and valid for linearity, precision, accuracy and robustness. Retention times were as follows: caffeine 2.57±0.02 min, theophylline 2.18±0.03 min, retinol 2.91±0.02 min, L-carnitine 3.0±0.009 min and Co-enzyme Q10 3.15 ±0.003 min. From the in vitro diffusion studies of active compounds alone, caffeine within all formulations had the highest diffusion rate compared to theophylline and L-carnitine (caffeine>theophylline>L-carnitine). Retinol and Co-enzyme Q10 did not diffuse across the skin within a 24-hour time-period. In combination with Co-enzyme Q10, the diffusion of caffeine increased from both gel and cream formulations (p<0.05), while retinol increased the diffusion of theophylline from a liquid formulation (p<0.05). Theophylline increased the diffusion of L-carnitine from both liquid and gel formulations (p<0.05). Liquid and gel formulations without compounds, decreased the skin’s integrity after 24 hours and 2 hours, respectively. After 24 hours, the skin’s integrity decreased after exposure to all compounds tested (liquid and gel formulations), while the cream formulation mostly kept the integrity of the skin intact. Caffeine accumulated much more in the skin (>13%) compared to all the other compounds (<2.5%) for all three different formulations tested (caffeine>>L- carnitine>theophylline>retinol>Co-enzyme Q10). Combination studies mostly caused a decrease in accumulation of all compounds within the skin, except the following: retinol increased theophylline accumulation from a gel formulation and vice versa, Co-enzyme Q10 increased caffeine accumulation from all formulations and L-carnitine’s accumulation mostly increased when combined with other compounds. Conclusion: Caffeine was found to diffuse across and accumulate within the skin to a higher extent as compared to all the other compounds due to its ideal physicochemical characteristics. Very lipophilic compounds like retinol and Co-enzyme Q10 only accumulated to some degree in the skin. The findings indicated that the preferable combinations to increase efficacy, would be Co-enzyme Q10 in combination with caffeine, especially from a cream formulation, retinol in combination with theophylline (gel) and any of the compounds combined with L-carnitine (gel and cream). Cognisance must however be taken about possible systemic side effects
A dissertation submitted in fulfillment of the requirements of the degree of Master of Science in Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg 2023
Keywords: Skin afflictions; Porcine skin; SDG-3: Good health and well-being